Alternative Method for Calculating Service Level Agreements for Internet Access Services in Rural Areas - Edward, Ian Josef Matheus; Situmorang, Hamonangan; Fajrin, Noer; Alfarobby, Daffa F.; Royyan, Aulia; Nur Muhammad, Jabar (Ital Publication, 2025)
Indonesia faces significant challenges in providing equitable internet access, particularly in remote areas. To address these challenges, the government collaborates with private Internet Service Providers (ISPs) under Service Level Agreements (SLAs) that define key service metrics, such as uptime and response time. Network Management System A (NMS A), managed by the government, handles telecommunications infrastructure, while NMS B, operated by the private ISP, delivers the internet services. A critical challenge in assessing SLA performance is distinguishing between service disruptions caused by network issues and those caused by power outages. This study proposes an SLA calculation method that prioritizes uptime data from NMS A, reflecting the government's perspective. If NMS A’s data is unavailable, UPS data is used as an alternative. NMS B’s data is considered only if its correlation with NMS A is strong (≥0.6). Additionally, the study classifies downtime: link failures exceeding 300 seconds require compensation (restitution). Downtime less than or equal to 300 seconds is considered non-restitution, and no compensation is needed. Power outages are considered non-restitution events, as they stem from external factors beyond the service provider's control. This method has been tested in over 1,000 locations, proving its reliability and adaptability for fair, transparent SLA evaluations.